Construction of engineering microorganism degrading chlorophenol efficiently by protoplast fusion technique. Issue 3 (23rd March 2012) - Chen, Honglei; Zhan, Huaiyu; Chen, Yuancai; Fu, Shiyu
<x xml:space="preserve">Abstract</x> Protoplast fusion is an important technique for engineering microbial strains. It has been used to combine genes from different organisms to create new strains with desired properties. This investigation was aimed to construct a new strain with an ability of degrading chlorophenols efficiently by protoplast fusion between Pseudomonas putida and Psathyrella candolleana. Twenty recombinant strains were screened and used to degrade pentachlorophenol (PCP) synthetic wastewater in order to determine their capabilities of chlorophenol degradation. To rapidly and accurately measure PCP content in synthetic wastewater after treatment by different strains, a new method quantifying PCP was proposed based on derivative spectroscopy. Chlorophenol biodegradability of different strains could be measured rapidly according to the new method. The results showed that PCP degradation % of four recombinant strains viz., Xz 6‐1, Xz 6‐3, Xz 6‐5, Xz 8‐2 were 78.98%, 69.12%, 31.40%, 46.26%, respectively, and that of parent strain (Pseudomonas putida.) was 57.27%, which indicated that the degradation % of Xz 6‐1 is the highest and improved by 21.71% compared with Pseudomonas putida. Furthermore, the colony morphologies and microscopic feature of Xz 6‐1 and Pseudomonas putida were compared in this article. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 443–448, 2013